Aktywność podmiotów polityki lokalnej w zakresie prywatyzacji jednostek sektora publicznego - Wojarska, Magdalena; Wędrowska, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main aim of that article is an identification of local authorities level engagement in privatization process as well as the factors which determine their activity.The empirical data show that local authorities engagement in state enterprises privatization have been caused by: goals regional policy in the field of infrastructure development, range of investments making by other investors and municipal authorities activity in the field of local economic subjects elicitation and the kind of business. On the other hand, local authorities have privatized the municipal enterprises when there was such necessity and it has not been influenced by any conditions. (original abstract
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 715-722